Alimentación y religión en una morería valenciana bajomedieval: Castelló de la Plana - Díaz de Rábago, Carmen (Millars. Espai i Història, 2018)
Coexistence of several religious confesions in the late medieval Kingdom of Valencia provoked frictions between them. These frictions were often manifested through several social habits. Meatst consume, with its ritual character, met points of divergence among the several religious confessions. Qn the other hand, meat consume in late medieval Valencia is related with a process of improvement of the diet, as we can see in the historical sources of the Municipal archive in Castellón for the fifteenth century.